‘Making the invisible visible’ through alcohol screening and brief intervention in community pharmacies: an Australian feasibility study - Hattingh, Laetitia; Hallett, Jonathan; Tait, Robert (BioMed Central Ltd, 2016)
Background: Screening and brief interventions (SBI) for alcohol related problems have been shown to be effective in health settings such as general practice or emergency departments. Recent data from the United Kingdom and New Zealand suggest that SBI can be delivered through community pharmacies, but this approach has not been tested in Australia. This study assesses the feasibility of delivering alcohol SBI via community pharmacists. Method: We recruited five pharmacies and developed an SBI training package to be delivered by pharmacy staff, who screened consumers and delivered the brief intervention where appropriate. Consumers also completed a questionnaire on the process. At three months consumers were telephoned to enable ‘retention’ to be quantified. After completing recruitment, a semi-structured interview was conducted with pharmacists on the process of delivering the intervention, potential improvements and sustainability. Results: Fifty consumer participants were screened, ten from each pharmacy. There were 28 (57 %) men and 21 (43 %) women with one not responding. Most (67 %) were aged 25-55 years. Their AUDIT scores had a range of 0 to 39 (mean 10.9, SD 9.8) with 11 categorised as ‘hazardous (8-15)’, four as ‘harmful (16-19)’ and eight as ‘probably dependent (20+)’ consumers of alcohol. Reactions to the process of SBI were generally favourable: for example 75 % agreed that it was either appropriate or very appropriate being asked about their alcohol consumption. With respect to follow-up interviews, 23 (46 %) agreed that they could be contacted, including five from the highest AUDIT category. Subsequently 11 (48 %) were contactable at three months. Three of the five non-low risk drinkers had reduced their level of risk over the three months. Ten pharmacists participated in semi-structured telephone interviews. Overall these pharmacists were positive about the intervention and five main themes emerged from the interviews: 1) flexibility applied in recruitment of participants, 2) easiness in use of AUDIT score to facilitate discussions, 3) perceived positive intervention impact, 4) enhanced role of community pharmacists and 5) facilitators and challenges experienced. Conclusions: Pharmacy-based SBI appears to be acceptable to consumers and feasible for pharmacy staff to deliver. Challenges remain in translating this potential into actual services.